2011
DOI: 10.1590/s1808-86942011000300020
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologic manifestations in HIV disease: clinical aspects and treatment

Abstract: HIV is a pandemic infection with cases notified in almost all countries. The reported prevalence of symptoms in the head and neck is about 80%; otolaryngologists may be the first physician to see such patients. Oral manifestations are the most common, followed by neck and sinus manifestations. Otolaryngologic symptoms may be important signs of antiretroviral therapy failure. Symptoms are present in acute infections and advanced cases. Objective To describe new approaches in the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 53 publications
3
19
0
19
Order By: Relevance
“…In the other developing countries, oral candidiasis was most prevalent, followed by aphthous ulcers and stomatitis. [10,12] All studies, including ours, showed high rates of cervical lymphadenopathy, head and neck lymph nodes being common signs of systemic disease. [10,12] However, our study is the only one to have documented parotid gland cystic enlargement, revealing that this is an early (WHO stage I or II) manifestation, when immunity is well preserved.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In the other developing countries, oral candidiasis was most prevalent, followed by aphthous ulcers and stomatitis. [10,12] All studies, including ours, showed high rates of cervical lymphadenopathy, head and neck lymph nodes being common signs of systemic disease. [10,12] However, our study is the only one to have documented parotid gland cystic enlargement, revealing that this is an early (WHO stage I or II) manifestation, when immunity is well preserved.…”
Section: Discussionmentioning
confidence: 67%
“…[10,12] All studies, including ours, showed high rates of cervical lymphadenopathy, head and neck lymph nodes being common signs of systemic disease. [10,12] However, our study is the only one to have documented parotid gland cystic enlargement, revealing that this is an early (WHO stage I or II) manifestation, when immunity is well preserved. Moreover, parotid enlargement is known in the community to be associated with HIV; recognising it as a stigma of infection, patients are motivated to seek a diagnosis and possible cosmetic treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It is important to emphasize that the existing abnormalities may occur due to the action of the virus upon the body, the immunosuppression and presence of opportunistic infections, as well as the action of antiretroviral medication and potentially ototoxic medication (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)24) . The specialized literature has shown widely diversified results concerning the occurrence of hearing loss in the population with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Many different studies in the literature refer that the most frequently observed type of hearing loss in HIV/AIDS adults is sensorineural (5,14,21,24) , followed by conductive hearing loss (21) , and that the impairment is normally bilateral and progressive (2,9,15) . Concerning middle ear impairment, and consequently, presence of conductive or mixed hearing loss, some studies report that this impairment would result from immunosuppression, which favors the presence of opportunistic infections (25) .…”
Section: Discussionmentioning
confidence: 99%